Carbon Nanotubes Disrupt Iron Homeostasis and Induce Anemia of Inflammation through Inflammatory Pathway as a Secondary Effect Distant to Their Portal‐of‐Entry. Issue 15 (13th February 2017) - Ma, Juan; Li, Ruibin; Liu, Yin; Qu, Guangbo; Liu, Jing; Guo, Wenli; Song, Haoyang; Li, Xinghong; Liu, Yajun; Xia, Tian; Yan, Bing; Liu, Sijin
Abstract : Although numerous toxicological studies have been performed on carbon nanotubes (CNTs), a few studies have investigated their secondary and indirect effects beyond the primary target tissues/organs. Here, a cascade of events are investigated: the initiating event and the subsequent key events necessary for the development of phenotypes, namely CNT‐induced pro‐inflammatory effects on iron homeostasis and red blood cell formation, which are linked to anemia of inflammation (AI). A panel of CNTs are prepared including pristine multiwall CNTs (P‐MWCNTs), aminated MWCNTs (MWCNTs‐NH2 ), polyethylene glycol MWCNTs (MWCNTs‐PEG), polyethyleneimine MWCNTs (MWCNTs‐PEI), and carboxylated MWCNTs (MWCNTs‐COOH). It has been demonstrated that all CNT materials provoke inflammatory cytokine interleukin‐6 (IL‐6) production and stimulate hepcidin induction, associated with disordered iron homeostasis, irrespective of exposure routes including intratracheal, intravenous, and intraperitoneal administration. Meanwhile, PEG and COOH modifications can ameliorate the activation of IL‐6‐hepcidin signaling. Long‐term exposure of MWCNTs results in AI and extramedullary erythropoiesis. Thus, an adverse outcome pathway is identified: MWCNT exposure leads to inflammation, hepatic hepcidin induction, and disordered iron metabolism. Together, the combined data depict the hazardous secondary toxicity of CNTs in incurring anemia through inflammatory pathway. This study will also open a new avenue for future investigations on CNT‐induced indirect and secondary adverse effects. Abstract : Exposure of multiwall carbon nanotubes alters hepatic hepcidin‐mediated systemic iron homeostasis through pro‐inflammatory responses in mice, leading to limited iron availability for red blood cell formation and eventually the development of anemia of inflammation. This study opens a new path to understand the biological impacts of carbon nanotubes through their secondary or compensatory effects beyond the primary target tissues/organs.